Learning styles and academic performance among nursing and midwifery students: A cross-sectional study - Mohammadreza Rajabloo; Hamideh Mancheri; Ali Kavosi; Zahra Sabzi (Journal of Nursing Advances in Clinical Sciences)
The primary mission of medical education is to train competent individuals who can enhance and maintain community health. Given the significant role of learning styles in education and their potential impact on student’s academic performance, this study aims to determine the relationship between learning styles and academic performance among nursing and midwifery students. This cross-sectional study was conducted in 2023 in Gorgan, Iran. The research population consisted of nursing and midwifery students at Golestan University of Medical Sciences, with a total sample size of 386 selected through census sampling. Data were collected using demographic forms and Kolb’s Learning Style Inventory. The data were analyzed using SPSS software version 18, employing Pearson correlation, Kruskal-Wallis, and Mann-Whitney tests, with a significance level set at 0.05. The results revealed that the mean age of the participants was 22.45 (SD=3.13) years. Regarding gender, 201 participants (52.1%) were female, and 158 (47.9%) were male. The predominant learning style among students was Concrete Experience (23.15 [SD=7.85]). The Spearman correlation test indicated no significant relationship between learning style dimensions and age or the grade point average. The Mann-Whitney test revealed significant differences in experimental learning styles based on field of study (P=0.003) and gender (P=0.04). The predominant learning style among the nursing and midwifery students studied was Concrete Experience. Therefore, by recognizing the impact of these factors on student learning, challenges and opportunities in this area can be identified. This understanding can lead to practical steps toward improving the quality of educational programs and assisting educators in lesson planning in the classroom.